A new δεκαστάδιον (milestone) from Amphipolis - Nigdelis, Pantelis; Anagnostoudis, Pavlos (Tekmeria, 2017)
The article presents a dekastadion (σταδιοδείκτης, milestone, Distanzanzeiger) that was recently found in the area of Amphipolis. Thanks to the new inscription, the number of dekastadia originating from pre-Roman Macedonia increases now to five. The new find confirms that in pre-roman Macedonia the road between Amphipolis and Philippi was passing along the north side of Mount Pangaion, as it did in the later Via Egnatia. It also suggests that the central government had direct control over the construction and maintenance of road infrastructures in the Kingdom of Macedon.